Contribution of a1-adrenoceptor subtypes in renal hemodynamics and functions of rats with renal impairment : alteration of g-protien linked to shift in the functionality And expression of renal a1-adrenoceptor subtypes. - Abdul Sattar, Munavvar Zubaid (Universiti Sains Malaysia, 2013)

(untitled)
This study investigated the role of a 1-adrenoceptors subtypes in the regulation of renal haeamodynamics at the level of renal resistance vasculature. It is hypothesized that a 1- adrenoceptor subtype(s) distribution depends on pathophysiological states of animal. Thus, the functional role of a 1-adrenoceptor subtype(s) on renal haeamodynamics of rats with renal failure, diabetic nephropathy and cardiac hypertrophy was investigated along with the Go proteins expression in the kidney and heart of normal rats and that of rats with impairments.